2001
DOI: 10.1002/1097-0142(20010601)91:11<2084::aid-cncr1236>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Angiography effectively supports the diagnosis of hepatic metastases in medullary thyroid carcinoma

Abstract: BACKGROUND Medullary thyroid carcinoma (MTC) belongs in the group of neuroendocrine tumors with early lymphatic and hepatic dissemination. A high rate of undetectable metastases is hypothesized to be responsible for the frequent mismatch between the apparent relatively small tumor burden and the elevated plasma tumor marker level. METHODS Thirty‐six MTC patients with residual/recurrent biochemical signs (elevated basal calcitonin level) and/or characteristic general symptoms (diarrhea and/or flushing) were sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 55 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Indeed, Simeone et al (33) reported a 96% sensitivity and 83% specificity. Moreover, because our gold standard included imaging follow-up, sensitivity of CT for liver exploration should be probably lower if patients had undergone hepatic arteriography, MRI, or laparoscopic liver biopsy, which showed higher sensitivity than CT in previous studies (14,34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Simeone et al (33) reported a 96% sensitivity and 83% specificity. Moreover, because our gold standard included imaging follow-up, sensitivity of CT for liver exploration should be probably lower if patients had undergone hepatic arteriography, MRI, or laparoscopic liver biopsy, which showed higher sensitivity than CT in previous studies (14,34).…”
Section: Discussionmentioning
confidence: 99%
“…If Ct is more than 400 pg/ml then multiphase CT liver protocol, contrast-enhanced MRI of the liver, MRI of the spine, bone scintigraphy, and 18 F-FDG PET may be considered [3,8,10,11]. The insensitivity of imaging has been attributed to small hypervascular hepatic metastases detected only on hepatic arteriography in a significant number of patients [16,17], which in one study reached 89% [34]. Therefore, the use of staging laparoscopy to detect surface metastases, hepatic venous sampling, and hepatic angiography has been previously investigated; however, all of these techniques should be used sparingly.…”
Section: Surveillancementioning
confidence: 98%
“…Normalization of serum calcitonin, for the most part, is not feasible when more than two lymph node compartments, or 10 and more lymph nodes, are involved, presumably due to the presence of distant metastases [54, 57, 59]. Occasionally, occult distant metastases can be localized with the use of invasive procedures, namely venous cathetherization [68–70], thoracoscopy, laparoscopy [71], hepatic angiography [72] and radioimmunoguided surgery [73].…”
Section: Nodal Metastasis Mode Of Spread and Distant Metastasismentioning
confidence: 99%